Ketupat Kandangan: Simbol Nilai-Nilai Islam dalam Kuliner Banjar dan Implikasinya terhadap Identitas Budaya serta Ekonomi Lokal - Zaki, Muhammad; Ratnaningsih, Nani; Marwanti, Marwanti (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2024)
Ketupat Kandangan, a traditional Indonesian dish from South Kalimantan, embodies the harmonious integration of Islamic values, cultural heritage, and economic sustainability in Banjar society. This study explores the significance of Ketupat Kandangan as a symbol of Islamic principles such as togetherness (ukhuwwah Islamiyyah), simplicity (zuhud), and gratitude (syukur), which are reflected in its preparation and consumption during religious and social gatherings. Through qualitative research methods, including observations, interviews, and documentation, this study analyzes the role of Ketupat Kandangan in preserving cultural identity, strengthening social cohesion, and supporting the local economy. The findings reveal that the communal aspect of preparing and sharing the dish reinforces Islamic values and cultural transmission, while the use of local ingredients supports farmers, fishermen, and culinary entrepreneurs. However, challenges such as limited shelf life and declining interest among younger generations necessitate modern innovations in packaging, marketing, and educational initiatives. The study emphasizes the importance of collaborative efforts among stakeholders to ensure the sustainability and competitiveness of Ketupat Kandangan as a cultural icon and economic driver. By embracing modernization while staying true to its Islamic and cultural roots, Ketupat Kandangan serves as an example of how traditional cuisine can be leveraged to strengthen both cultural identity and economic development in the face of globalization.